2018
DOI: 10.1111/joca.12176
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Value Co‐Creation Wellness Model: The Role of Physicians and Digital Information Seeking on Health Behaviors and Health Outcomes

Abstract: The US health care system lags behind other developed nations in health advances for chronic diseases. Thus, decreasing the prevalence of preventable chronic diseases has significant implications for individuals and society. Using service‐dominant logic and value co‐creation theory, the authors develop and test a health co‐creation framework that investigates how access to primary care and patient information seeking affect pro‐health behavioral changes and other mutually valued health outcomes. The findings p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 111 publications
(191 reference statements)
0
27
0
Order By: Relevance
“…To avoid or reduce the probable halo effect, we would advise healthcare and consumer welfare advocates to clearly inform people and prevent them from envisaging some imaginary collateral effects. Since in our study the experiments are based on science communication through digital channels like websites and blogs, we consider that consumer advocacy groups also need to guide consumers on the use of the various digital information sources (Adams et al ., 2015; Dahl et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid or reduce the probable halo effect, we would advise healthcare and consumer welfare advocates to clearly inform people and prevent them from envisaging some imaginary collateral effects. Since in our study the experiments are based on science communication through digital channels like websites and blogs, we consider that consumer advocacy groups also need to guide consumers on the use of the various digital information sources (Adams et al ., 2015; Dahl et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To answer these research questions, the present study adopts a qualitative approach based on in‐depth interviews with Instagram male fitness hashtag users aiming to explore their motivations for body image transformation and the consequences on their behavior and wellbeing. The present study lies within transformative consumer research, which focuses on significant social issues and challenges such as health and nutrition (Dahl et al ., 2018). On top of that, digital information seeking can affect physical activity and dietary health behavior and also mental wellbeing (Dahl et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dahl et al undertook an analysis, based on structural equation modeling, of data received from a sample of 392 adult participants in a Country Wellness Rankings study carried out in one of the Midwestern states. They reported that access to primary care might increase the search for digital information, and this, in turn, may lead to changes in health behaviors and improved overall physical health [ 77 ].…”
Section: Discussionmentioning
confidence: 99%